Amplificador operacional de transcondutância totalmente diferencial com alta linearidade e circuito de compensação de modo comum - Freitas, João Pedro Gonçalves (2019)
In this work, we present the design of a fully differential Operational Transconductor Amplifier (OTA) with high linearity, based on the Folded Flipped Voltage Follower (FFVF) Topology. This structure was developed and applied on a 3a order low-pass Gm − C filter, based on the Chebyshev’s aproximation with a cutoff frequency of 300 kHz. Besides that, the OTA has low differential offset and it is integrated with a common mode feedback compensation circuit, to eliminate the common mode voltage at the output nodes. The project was implemented in a 0.35 µm Complementary Metal-Oxide-Semiconductor (CMOS) technology and operates at a + −1.5 V power supply.